Play therapy in perspective theory of eco systemic therapy - Sofwan Adiputra; Mujiyati Mujiyati (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2017)
Play therapy is a counseling approach for children applying toys, games, and otherplay media to communicate to the children